On the Availability of the Decoy State BB84 QKD over a Terrestrial FSO Link - Ntanos, Argiris; Zavitsanos, Dimitris; Lyras, Nikolaos K.; Giannoulis, Giannis; Avramopoulos, Hercules (2021 International Conference on Optical Network Design and Modeling (ONDM), 2021)
A research contribution focusing on the feasibility of the Decoy State BB84 Quantum Key Distribution (QKD) protocol over a free-space optical (FSO) link under strong and moderate solar radiance in the urban environment of Athens city, Greece for short distances up to 1km is presented. Emphasis is placed on the time varying attenuation which is introduced by various atmospheric processes and especially on the effect of strong atmospheric turbulence. We examine how these factors affect the performance of the FSO link by conducting numerical simulations of the Secure Key Rate (SKR) and evaluating the link availability.